(3JNejS GdHQOIs - (3eMeO agei YHO Gddg GdehUdj GdTgjQ HeMVQ HGTG RGOIs; (3GdHhUjQj,J (B696 (3g` s
(3ChdgG (B:s
(3GeG HYO c ajbhd deG QCjJ GdTjN ddTgjQ Ydi CdSfII GdfGS GdHhUjQi jG ef CHg HbdH HGJ ai SdGe hOeYg Hjf efgd hefSLe s
(3BNQgG (B:s
(3hGdBd hGdUMH WQG ef MhhGQJfG hGdJGHYjf GdcQGe GdSGOI GdfLHG hcd ef bO fCi ai GdOjf hGbJQHG WQfMJ YPHGJ GddHGf QjM UHG hCWQH GdYjS MGOi GdYjS HGdfZe s
(3Vef eLehY s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3JNejS TYQis
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs